2022
DOI: 10.1021/acs.jafc.2c00828
|View full text |Cite
|
Sign up to set email alerts
|

New Monoterpene Acid and Gallic Acid Glucose Esters with Anti-Inflammatory Activity from Blue Gum (Eucalyptus globulus) Leaves

Abstract: Blue gum (Eucalyptus globulus) is a widely used botanical in the cosmeceutical and food industries. Although blue gum leaves are known for abundant essential oils, their nonvolatile phytochemical constituents and bioactivities remain unclear. Herein, a phytochemical investigation of blue gum leaves led to the identification of eight new monoterpene acid and gallic acid glucose esters (1−4 and 14−17; glubosides A−H, respectively) and 12 known analogues (5−13 and 18−20). Their structures were determined based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The compound 1,8-cineole demonstrated the downregulation of inflammatory responses in dextran sulfate sodium (DSS)-induced colitis in mice and decreased proinflammatory chemokine production in TNF-stimulated HT-29 cells, proving to be a potent compound in treating human IBD [53]. Monoterpene acid and gallic acid glucose esters and phenolic compounds have also been reported in Eucalyptus species, which have shown a substantial reduction in the production of pro-inflammatory cytokines, including TNF, IL-1β, and IL-6 in LPS-stimulated peripheral blood mononuclear cells (PBMCs) and LPS-stimulated murine macrophage (RAW264.7) cells, indicating significant anti-inflammatory effects [54,55]. Studies have also reported the presence of phenolic compounds (including flavonoids, phenylpropanoids, and polyphenols) [56][57][58] and triterpenoids (including lupine, ursane, and oleanane derivatives) in Melaleuca species [59][60][61][62].…”
Section: Plant-derived Anti-inflammatory Compoundsmentioning
confidence: 99%
“…The compound 1,8-cineole demonstrated the downregulation of inflammatory responses in dextran sulfate sodium (DSS)-induced colitis in mice and decreased proinflammatory chemokine production in TNF-stimulated HT-29 cells, proving to be a potent compound in treating human IBD [53]. Monoterpene acid and gallic acid glucose esters and phenolic compounds have also been reported in Eucalyptus species, which have shown a substantial reduction in the production of pro-inflammatory cytokines, including TNF, IL-1β, and IL-6 in LPS-stimulated peripheral blood mononuclear cells (PBMCs) and LPS-stimulated murine macrophage (RAW264.7) cells, indicating significant anti-inflammatory effects [54,55]. Studies have also reported the presence of phenolic compounds (including flavonoids, phenylpropanoids, and polyphenols) [56][57][58] and triterpenoids (including lupine, ursane, and oleanane derivatives) in Melaleuca species [59][60][61][62].…”
Section: Plant-derived Anti-inflammatory Compoundsmentioning
confidence: 99%